2014
DOI: 10.1021/jp4103614
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of TiO2 Blocking Layers for Dye-Sensitized Solar Cells

Abstract: Thin compact layers of TiO2 are grown by thermal oxidation of Ti, by spray pyrolysis, by electrochemical deposition, and by atomic layer deposition. These layers are used in dye-sensitized solar cells to prevent recombination of electrons from the substrate (FTO or Ti) with the hole-conducting medium at this interface. The quality of blocking is evaluated electrochemically by methylviologen, ferro/ferricyanide, and spiro-OMeTAD as the model redox probes. Two types of pinholes in the blocking layers are classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
296
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(311 citation statements)
references
References 59 publications
(174 reference statements)
15
296
0
Order By: Relevance
“…Various conventional methods including spin coating, 18 spray pyrolysis, 19,20 electrochemical deposition 21 and thermal oxidation 22,23 were used to prepare a TiO 2 compact layer. With these methods, thermal post-treatments at high temperature (>450 C) are required to ensure adequate electronic contact.…”
mentioning
confidence: 99%
“…Various conventional methods including spin coating, 18 spray pyrolysis, 19,20 electrochemical deposition 21 and thermal oxidation 22,23 were used to prepare a TiO 2 compact layer. With these methods, thermal post-treatments at high temperature (>450 C) are required to ensure adequate electronic contact.…”
mentioning
confidence: 99%
“…22 Impedance spectroscopy measurements of the PEC cell, as shown in Figure S7, revealed a nonlinear capacitive behavior of the anodic interface, supporting the idea of charge carrier accumulation at interfaces. 29 We consequently introduced a model for surface states, which are expected due to the reactivity and high surface-to-volume-ratio of the porous electrode. 6 Previous experimental results from Rongéet al suggested that the photocurrent was controlled by two parallel adsorption processes.…”
Section: Preparation Of Electrodes and Membrane Electrode Assembly (Mmentioning
confidence: 99%
“…Doping level of the TiO 2 compact layer can be measured by employing an electrochemical three-electrode setup in which FTO/TiO 2 forms the working electrode. 12 A suitable electrolyte plays the contacting role of the perovskite layer in solar cells. Capacitance measurements are shown in Fig.…”
mentioning
confidence: 99%